The Perception of South African Adolescents Regarding Primary Health Care Services - Magdalena S. Richter; Vivian Mfolo (The Scientific World Journal)
Most of the South African public health facilities fail to provide adolescent-friendly health services. A quantitative, descriptive research study was conducted at Stinkwater, a rural area in Hammanskraal, South Africa. The objective of the study was to describe the adolescent's preferences regarding primary health care services. A survey was conducted among 119 adolescents. It was found that adolescents wished to be involved in the planning of the activities of the adolescent health service, and that friendliness and respect for adolescents were seen as desirable characteristics of an adolescent-friendly health care service. Adolescents preferred services to be available throughout the week and to be located at the school, youth center, community center, hospital, or clinic. Health education was indicated as a priority and the health care team should include different members of a multidisciplinary team. Adolescents preferred that their health services be separated from adult services and that a male nurse be employed in the adolescent service in order to create a less feminine image. It was also recommended that all adolescents be educated about the types of services available. Understanding health care service preferences of adolescents is needed in order to deliver optimal health care to this group.